IMPLEMENTASI MEDIA PEMBELAJARAN BERBASIS WEB UNTUK MENDUKUNG LITERASI DAN NUMERASI DI ERA DIGITAL DI SDN HANDIL BAKTI 2 - Alim, Agus Alim Muin; Silvia Ratna; Erfan Karyadiputra; Agus Setiawan; Sefto Pratama; Nadiya Hijriana (Jurnal Inovasi Pengabdian Masyarakat, 2024)
The availability of professional human resources, especially teachers, is the most important capital to improve the quality of human resources, especially in the field of education, therefore efforts are needed to improve the understanding and ability of teaching staff in keeping up with information technology developments and utilizing these technological facilities in teaching and learning activities in schools. Education in the digital era requires innovative approaches to improve students' literacy and numeracy. One of the solutions carried out is the implementation of web-based learning media, which has great potential in supporting the learning process in the midst of the dynamics of technological developments. This service aims to explain and analyze the implementation of learning media using web-based canva as an effort to support literacy and numeracy in the digital era. Presentation methods, training and independent practice are the methods used so that teachers can make interesting percentages, learning videos, storybooks, worksheets on literacy and numeracy themed subjects based on the web after the implementation of a series of skill development training activities and skills to teachers at SDN Handil Bakti 2, there is an increase in the abilities and skills of teachers by an average of 59% in terms of making Web-Based media to support Literacy and Numeracy in the Digital Era